A nested sum is one in which one summation is inside another. Let the function f ( m , n ) be equal to the nested sum a 1 = 1 ∑ m ( a 2 = 1 ∑ a 1 ( a 3 = 1 ∑ a 2 ( ⋯ ( a n − 1 = 1 ∑ a n − 2 ( a n = 1 ∑ a n − 1 a n ) ) ⋯ ) ) ) . For how many values of n ≤ 1 0 0 0 will f ( m , n ) ∣ f ( m + 1 , n ) if m = 1 1 ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
How is f ( m , 1 ) = m − 1 ? Isnt f ( m , 1 ) = a 1 = 1 ∑ m a 1 = 2 m ( m + 1 ) ?
Log in to reply
Oh yes, you're correct! It should've been f ( m , 0 ) = m − 1 . That demands a slight change of my arguments, but my logic is still true in its core.
This problem seems like a generalization of a problem I made a long time ago.
Problem Loading...
Note Loading...
Set Loading...
First, note that f ( m , n ) can be defined recursively as follows. ⎩ ⎨ ⎧ f ( m , n ) = m − 1 f ( m , n ) = k = 1 ∑ m − 1 f ( m − k , n − 1 ) if n = 1 if n > 0 We try to find another function which satisfies the same recursion.
Let g ( m , n ) denote the number of positive integer solutions to the equation a 1 + a 2 + ⋯ + a n + 1 = m . Note that when n = 1 , g ( m , n ) is simply the number of positive integer solutions to a 1 + a 2 = m . Each choice of a 1 determines a unique a 2 , and a 1 must lie in the range [ 1 , m − 1 ] for both a 1 and m − a 1 to be positive, which shows that g ( m , 1 ) = m − 1 .
We shall now show that g ( m , n ) = k = 1 ∑ n − 1 g ( m − k , n − 1 ) . Consider the equation a 1 + a 2 + ⋯ + a n + 1 = m . Let's say we fix the variable a n + 1 . If a n + 1 = 1 , the equation becomes a 1 + a 2 + ⋯ + a n = m − 1 , which has g ( m − 1 , n − 1 ) solutions by our definition. Similarly, if a n + 1 = 2 , the equation becomes a 1 + a 2 + ⋯ + a n = m − 2 , which has g ( m − 2 , n − 1 ) solutions. In general, if a n + 1 = k , the equation a 1 + a 2 + ⋯ + a n = m − k has g ( m − k , n − 1 ) solutions. Since a n + 1 ∈ { 1 , 2 , ⋯ , m − 1 } , we conclude that g ( m , n ) = k = 1 ∑ m − 1 g ( k − 1 , n − 1 ) .
Notice that g ( m , n ) has the same initial values of f ( m , n ) and they both follow the same recursion. A simple inductive argument shows that f ( m , n ) and g ( m , n ) are identically equal. But from stars and bars formula, we know that g ( m , n ) = ( n + 1 m + n ) . Hence, f ( m , n ) = ( n + 1 m + n ) ∀ ( m , n ) ∈ N 2 .
Then, note that f ( 1 1 , n ) f ( 1 2 , n ) = ( n + 1 1 1 + n ) ( n + 1 1 2 + n ) = 1 0 ! ( 1 1 + n ) ! 1 1 ! ( 1 2 + n ) ! = 1 1 1 2 + n .
It is easy to verify that there are 9 1 values of n in the range [ 1 , 1 0 0 0 ] which make the 1 1 1 2 + n an integer.